Tales of Styrnmouth - Kuenning, Licia (Farmington, ME : [Licia Kuenning], 2005)
"In my stories there's a ghost who made some mistakes in his lifetime that caused much more harm than he could fairly be blamed for. Like the rest of us, he couldn't foresee the consequences of his actions. He has to sort out which of his behaviors were morally wrong, which were merely errors, and which were good actions that unpredictably had bad results. In the process he sets more causes into motion, which in turn have effects of their own."--From the back cover.
Maine author. Licia Kuenning lives in Farmington, ME.
Keywords: Ghost stories, American; American fiction -- Quaker authors